2016
DOI: 10.1097/ajp.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status, Quality of Life, and Costs Associated With Fibromyalgia Subgroups

Abstract: We identified 3 distinct profiles which accounted for the heterogeneity of FM patients. Our findings might help to design tailored interventions for FM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
7
22
0
Order By: Relevance
“…The first study included a sample of 229 patients (ie, Sample 1) and the second study comprised a sample of 160 patients (ie, Sample 2). A detailed description of both studies’ protocols and inclusion/exclusion criteria can be found elsewhere . Of the total sum of patients, only those reporting severe levels of pain were included in the present study ( n = 385).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study included a sample of 229 patients (ie, Sample 1) and the second study comprised a sample of 160 patients (ie, Sample 2). A detailed description of both studies’ protocols and inclusion/exclusion criteria can be found elsewhere . Of the total sum of patients, only those reporting severe levels of pain were included in the present study ( n = 385).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of both studies' protocols and inclusion/exclusion criteria can be found elsewhere. 12,13 Of the total sum of patients, only those reporting severe levels of pain were included in the present study (n = 385). Following the methodology used by Suso-Ribera et al, 14 a score of 7 or higher in the pain intensity item of the Revised Fibromyalgia Impact Questionnaire (FIQR; item 12: "please indicate the intensity of the pain in the last 7 days, where 0 is no pain and 10 is unbearable pain") was used as a cut-off to select patients with severe pain levels.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In the present study, we utilized the dataset from the Fibromyalgia Subtypes study (Luciano et al, 2016 ) and early-stage data from the EUDAIMON study (Feliu-Soler et al, 2016 ). Study data are available from the corresponding author.…”
Section: Methodsmentioning
confidence: 99%
“…The heterogeneity of fibromyalgia has led to the proposal of the existence of subgroups of patients [88]; however, analgesic drug development is based on the mean responses of groups of patients with the same condition given the same drug and dose, with individual subjects or subgroups of the patient population given little consideration [89]. With such a heterogeneous condition, effectiveness is going to be dependent on multimodal pharmacology, as exhibited by amitriptyline.…”
Section: Discussionmentioning
confidence: 99%